Eikōn and Magic. Solomon’s Knot on the Floor Mosaic in Herakleia Lynkestis - Erdeljan, Jelena; Vranešević, Branka (IKON, 2016)
Abstract This paper discusses the iconography and apotropaic meaning and use of the motif of Solomon’s knot in Early Byzantine art. It focuses on the representation of this subject on the floor mosaic of the room attached to the baptistery by the Large Basilica in Herakleia Lynkestis, dating from the 6th century. In this catechumeneon Solomon’s knot is framed by repeating geometrical patterns of circles arranged in concentric rings and positioned within a field composed of squares and circles. This paper proposes that in this particular case the discussed aniconic motif can be observed as a sort of eikōn of the purification and salvation gained through baptism. At the same time, it remained deeply imbued with magical agency ascribed to the knot or seal of Solomon in texts of magical treatises which are known to have circulated in Byzantium in Christianized form.